2010
DOI: 10.1017/s1463423610000125
|View full text |Cite
|
Sign up to set email alerts
|

Rural interprofessional primary health care team development and sustainability: establishing a research agenda

Abstract: Primary health care (PHC) plays a pivotal role in health system reform locally and globally. The use of well functioning interprofessional primary health care (IPHC) teams is recognized as a key strategy in widespread health system reform across global, national, and provincial jurisdictions. IPHC teams contribute to the improvement of the health and well being of the population. These teams engage in issues that are a priority for citizens, such as: providing good evidence-based care; supporting the efforts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 76 publications
(130 reference statements)
0
10
0
1
Order By: Relevance
“…Earlier reviews have also more generally identified the need to consider contextual determinants (McCallin, 2001), and a range of systemic, organisational (top down) and individual (bottom up) factors (Lemieux-Charles and McGuire, 2006;San Martín-Rodríguez et al, 2005), especially in primary care settings (Bé langer and Rodrí-guez, 2008;McPherson and McGibbon, 2010;Xyrichis and Lowton, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Earlier reviews have also more generally identified the need to consider contextual determinants (McCallin, 2001), and a range of systemic, organisational (top down) and individual (bottom up) factors (Lemieux-Charles and McGuire, 2006;San Martín-Rodríguez et al, 2005), especially in primary care settings (Bé langer and Rodrí-guez, 2008;McPherson and McGibbon, 2010;Xyrichis and Lowton, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Reviews pertaining specifically to primary care teams include those conducted by Bé langer and Rodríguez (2008), Dinh (2012), McPherson and McGibbon (2010), Ruddy (2005) and Xyrichis and Lowton (2008). All conclude that interprofessional collaboration is complex.…”
Section: Interprofessionalmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, there are also many unknowns in terms of how to shift the QI culture within PHC service organizations at all levels while also shifting the way that practitioners, managers and funders have traditionally worked [15,28,50]. Thus, efforts to advance QI-PHC should carefully consider that QI is but one aspect of the health system and culture that is being shifted as many other features are concurrently being changed.…”
Section: Discussionmentioning
confidence: 99%